(untitled) (Janaki Medical College Journal of Medical Science, 2024)
Background & Objectives: Thumb accounts for 50% of the hand function. Amputation of the thumb severely jeopardises the hand function. Thumb replantation, toe transfer are the ideal methods for restoring the hand function, but is not always possible owing to type of injury, time to presentation, surgical skill and set up. Osteoplastic thumb reconstruction for amputation around the metacarpophalangeal joint is a good treatment option to restore the hand in a developing setup. Presentation of Case: A 25 yrs male with amputation of thumb around metacarpophalangeal joint with delayed presentation and crushing component of distal part underwent multiple staged osteoplastic reconstruction of the thumb. The procedures consisted of bony structure fixation with bone graft followed by coverage with a thinned tubed groin flap which was divided at 2 weeks interval. The thumb was made sensate with sensate flap (first dorsal metacarpal artery flap). Discussion: Thumb replantation is ideal in acute setup in a clean traumatic amputation, while toe transfer is ideal in a delayed setup with healed wound. This requires a good operating room set up with microsurgical set up and skilled manpower, which is difficult in a developing country. Osteoplastic reconstruction requires multiple staged procedures that can be done at a primary level setup. Conclusion: Osteoplastic thumb recontruction is a good option for amputation around the metacarpophalangeal joint to restore hand function in a resource limited set up.